The Grieving Process Experienced Family and Charges in Treating Children with Autism - Rizki Fitryasari Patra Koesoemo (Jurnal Ners, 2010)
Introduction: Children with autism will be a stressor to their family. This research aims to describe about family grieving process and family burden when taking care of their children with autism at Special Needs School Bangun Bangsa, Surabaya.Method: This research used descriptive phenomenology design with indepth interview method. The participant of this research was six member of a family who plays role as the main caregiver for autism child. This study employs the purposive sampling method. The data is gathered through interviews and fi eld notes that is then analyzed with the Collaizi technique. This research generated three themes.Result: The results illustrate families display the grieving process as a cycle. They feel a deep, permanent and long period of grief through in to five stages of grief: denial, anger, depression, bargaining and acceptance. The Grieving is come from the caregiver and the autism child. Large amounts of grief cause families in grief for a long period and this causes family burden. There are six family burden, psychological burden, physical burden, financial burden, social burden, time burden and thought burden.Conclusion: Finding of the research would hopefully be beneficial to professional health staff, especially psychiatric nurses to complete their ability in minimizing various negative impacts that the family may suffer from while taking care their autism children with autism through nursing care plans designs development, researches about family empowerment in burden managements and also a research to improve the Family Psycho-education Therapy and a specific Supportive Group Therapy modules for family with autism children.